Mass spectrometry-based metabolomics for discovering active ingredients and exploring action mechanism of herbal medicine - Guo, Sifan; Qiu, Shi; Cai, Ying; Wang, Zhibo; Yang, Qiang; Tang, Songqi; Xie, Yiqiang; Zhang, Aihua (Frontiers in Chemistry, 2023)
Natural products derived from herbal medicine is a fruitful source of lead compounds because of their structural diversity and potent bioactivities. However, despite the success of active compounds derived from herbal medicine in drug discovery, some approaches cannot effectively elucidate the overall effect and action mechanism due to their muti-component complexity. Fortunately, mass spectrometry-based metabolomics has been recognized as effective strategies to reveal the effect and discover active components, detailed molecular mechanism and multi-targets of natural products. Rapid identification of lead compounds and isolation of active components from natural products would benefit to facilitate new drug development. In this context, mass spectrometry-based metabolomics has established an integrated pharmacology framework for discovery of bioactivity-correlated constituents, target identification and action mechanism of herbal medicine and natural products. High-throughput functional metabolomics techniques could be used to identify natural product structure, biological activity, efficacy mechanisms, and their mode of action on biological processes, assisting bioactive leads discovery, quality control, and accelerate discoveries of novel drugs, and increasingly being developed in the era of big data, which use scientific language to clarify the detailed action mechanism of herbal medicine.